Vitiligo treatment with vitamins, minerals and polyphenol supplementation - Jalel Akrem; Soumaya Gaigi; Hamdaoui Mohamed (Indian Journal of Dermatology, 2009)
Background: Mammalian pigmentation results from the synthesis and accumulation of photo protective epidermal melanin. Melanin was formed from the amino acid precursor L-tyrosine within specialized cells, the melanocytes. Oxidative stress has been suggested to be the initial pathogenetic event in melanocyte degeneration with H 2 O 2 accumulation in the epidermis of patients with active disease. Auto immunity has been also suggested as another hypothesis in the pathogenesis of depigmentation disorders. Topical corticosteroids and phototherapy as common treatment modalities have been prescribed in patients with vitiligo. However, they are often not effective and safe (epidermal atrophy). Therefore, research for alternative therapies continues. Aims: To evaluate the beneficial effects of a supplementation with antioxidant vitamins (A, C, E) and minerals (zinc, selenium) for vitiligo treatment. Methods: Forty experimental autoimmune vitiligo mice C57BL6, aged from 5 to 12 months showing visible signs of induced vitiligo, were sequentially randomized into five parallel groups (8 mice per group). Each group mice was allocated an identical pre coded cage. the first group (SZV) received the ED+1,4 g zinc (Zn)+0.04 g selenium (Se)+vitamins (A 118 UI, C 8,5 mg, E 5,4 UI) /kg diet, the second group (PSZV) received the ED+1,4 g zinc (Zn)+0.04 g selenium (Se)+vitamins (A 118 UI, C 8.5 mg, E 5,4 UI)/kg diet+Polyphenol orally, the group 3 (PSZ ) received the ED+green tea decoction prepared from 100 g/l (polyphenol orally)+1,4 g Zn+0.04 g Se, the 4 (P) received the ED+green tea decoction prepared green tea decoction prepared from 100 g/l, the control group 5(C) received the ED++ distilled water. Cure was defined as repigmentation of treated sites. Photographic and optical techniques were used both at the baseline and on weekly basis. Results: By the end of the study, mices showed visible repigmentation. Using the investigator′s global assessment, therapeutic success in terms of a clear repigmentation documented in 70% of treated mice. Conclusion: Our findings suggest that an antioxidant supplementation is significantly beneficial in contributing superior clinical efficacy to cure vitiligo.